Study on interfacial adhesion of the aramid fibers/rubber matrix by grafting mercapto hyperbranched polysiloxane. (January 2020) - Yang, Xuan; Tu, Qunzhang; Shen, Xinmin; Jiang, Chengming; Pan, Ming; Zhu, Pengxiao; Li, Yi; Hu, Caibing; Zhang, Qiong
Abstract: In order to improve the interfacial adhesion between aramid fiber (AF) and rubber matrix, the mercapto hyperbranched polysiloxane (HPSi) was grafted onto the AFs via a novel in-situ growth strategy, which combines the formation of polydopamine (PDA) precursor layer and the co-dehydration condensation between (3-aminopropyl) trimethoxysilane and (3-mercaptopropyl) trimethoxysilane. Based on the results of characterizations including morphology observations and chemical structure analyses, the growth process of mercapto HPSi with the reaction time was investigated and discussed. The pull-out force tests of AFs/rubber composites, which were carried out by universal testing machine, showed that the modification strategy proposed in this study could increase the interfacial adhesion up to approximately 96.5%, and the key factor could be inferred to be the covalent interaction between mercapto groups and double bonds. It is also worth mentioning that the phenomenon of excessive surface modification will occur with the overlong growth time, which would result in the reduction of the interfacial adhesion. Highlights: Mercapto hyperbranched polysiloxane are grafted onto aramid fibers for the first time. The interfacial adhesion of composites increases by 96.5% via the surface modification. The effects of dehydration condensation reaction time on the growth of HPSi are investigated. The improvement mechanism of interfacial adhesion is studied. The strategy proposed in the paper has the universality for high-performance fibers.